Risk management approach on selected key companies listed on the Kuala Lumpur Stock Exchange - Pek, Thian Kor (2001)
This study tries to identify risks and exammes the vulnerability and the impact of companies listed on the KLSE exposed to various risk namely interest rates risks, currency risks, liquidity risks, business risks, commodity risks, market risks, credit risks and operational risks. Companies book and bottomlines are employed and compared against previous years or to their peers within the same sector in the country of against foreign countries. The study tries to identify the necessary measures to be taken to manage risk effectively. Various forms of risk management to be taken include risk transfer, risk control, risk avoidance, risk reduction, risk financing, risk retention and risk sharing. Based on the study, the result of the analysis indicate that companies that do not borrow excessively particularly in foreign currency denominated loans, employed hedging instruments, avoid aggressive expansion and diversified their business base fared far better than companies that have done otherwise. This is evident during the 1997~ 1998 Asian Financial Crisis that actually brought many troubled companies down to knees. With the understanding of risk management, more comprehensive risks management technique could be employed to safeguard the profitability of companies and shareholders' wealth.